Peran Guru Pendidikan Agama Islam dalam Pembentukan Akhlak Siswa di SMA Al Irsyad Kota Tegal - Maulidin, Syarif; Munip, Abdul; Nawawi , Muhamad Latif (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
Islamic Religious Education (PAI) plays a crucial role in shaping the character and morals of students, particularly at the high school level. PAI teachers not only serve as educators of religious theory, but also as role models and mentors who assist students in internalizing Islamic values in their daily lives. In the face of globalization and various negative external influences, the role of PAI teachers becomes even more strategic in instilling noble morals, such as honesty, responsibility, and empathy towards others. Therefore, it is essential to examine how PAI teachers in schools can effectively shape students' character through approaches rooted in Islamic values. This study aims to explore the role of PAI teachers in shaping the moral character of students at SMA Al Irsyad in Tegal City. The study's informants consist of 15 individuals, including the school principal, PAI teachers, parents, and several students involved in PAI education. Data were analyzed using a qualitative approach, employing in-depth interviews and participatory observation techniques. Data validation was carried out through source triangulation, where the information obtained from interviews with teachers, students, and parents was compared and checked for consistency. The findings of the study indicate that PAI teachers at SMA Al Irsyad play a significant role in shaping students' character through an approach based on exemplary teaching, the habituation of Islamic values, and collaboration with parents to support character development. This research is expected to contribute to the development of character education methods based on religious values in Islamic schools and serve as a reference for religious education in shaping a generation with noble morals and religious devotion.